Observation of the decay Ξ−b→pK−K - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (American Physical Society, 2017)
Decays of the Ξ−b and Ω−b baryons to the charmless final states ph−h'−, where h(') denotes a kaon or pion, are searched for with the LHCb detector. The analysis is based on a sample of proton-proton collision data collected at center-of-mass energies √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb^−1. The decay Ξ−b→pK−K− is observed with a significance of 8.7 standard deviations, and evidence at the level of 3.4 standard deviations is found for the Ξ−b→pK−π− decay. Results are reported, relative to the B−→K+K−K− normalization channel, for the products of branching fractions and b-hadron production fractions. The branching fractions of Ξ−b→pK−π− and Ξ−b→pπ−π− relative to Ξ−b→pK−K− decays are also measured.